Farmers Group Dynamics Dumbo Catfish (Clarias Geriepenus) In The Hangtuah Village Of Perhentian District Kampar Regency Riau Province - Tati Hariati; Kusai '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in July 2014. This study aims to examine the factors that affect the group dynamics of each group of fish farmers and to determine the level of group dynamics in each group fish farmer. The method used in this study is a survey method with each group of respondents 10 respondents.The level of group dynamics in the Maju Bersama group is in the dynamic category with a score of 660 while the category Rezky Air group less dynamic with a score of 439. The results of this study indicate that factors the differences between the Maju Bersama groups and the Rizki Air group is the most important group goals. At the destination factor Maju Bersama group members and administrators want to jointly build a better business by way of aligning the price of fish production as well as a desire to grow their business. On Rezky Air group has a goal to get government assistance.Keyword: Group of farmers, less dynamic, dynamic score